Biomechanics of In-Stance Balancing Responses Following Outward-Directed Perturbation to the Pelvis During Very Slow Treadmill Walking Show Complex and Well-Orchestrated Reaction of Central Nervous System - Matjačić, Zlatko; Zadravec, Matjaž; Olenšek, Andrej (Frontiers in Bioengineering and Biotechnology, 2020)
Multiple strategies may be used when counteracting loss of balance during walking. Placing the foot onto a new location is not efficient when walking speed is very low. Instead medio-lateral displacement of center-of-pressure, rotation of body segments to produce a lateral ground-reaction-force and pronounced braking of movement in the plane of progression is used. It is however presently not known in what way these in-stance balancing strategies are interrelated. Twelve healthy subjects walked very slowly on an instrumented treadmill and received outward-directed pushes to the waist. We created experimental conditions where the use of stepping strategy to recover balance following an outward push was minimized by appropriately selecting the amplitude and timing of perturbation. Our experimental results showed that in the first part of the response the principal strategy used to counteract the effect of a perturbing push was a short but substantial increase in lateral ground-reaction-force. Concomitant slowing of the movement and related anterior displacement of center-of-pressure enabled lateral displacement of center-of-pressure which was, together with a short but substantial increase in vertical ground-reaction-force, instrumental in reducing the inevitable increase of whole-body angular momentum in the frontal plane. However, anterior displacement of center-of-pressure and increased vertical ground-reaction-force also induced an increase in whole-body angular momentum in the sagittal plane. In the second part of the response the lateral ground-reaction-force was decreased with respect to unperturbed walking thus allowing for a decrease of whole-body angular momentum in the frontal plane. Additionally, an increase in anterior ground-reaction-force in the second part of the response propelled the center-of-mass in the direction of movement, thus re-synchronizing it with the frontal plane component of the center-of-mass as well as decreasing whole-body angular momentum in the sagittal plane. The results of this study show that use of in-stance balancing strategies counteracts the effect a perturbing push imposed on the center-of-mass, re-synchronizes the movement of center-of-mass in sagittal and frontal planes to the values seen in unperturbed walking and maintains control of whole-body angular momentum in both frontal and sagittal planes.